Evaluation of root dilaceration and taurodontism in children with and without cleft lip and palate - BORAHAN, MEHMET OĞUZ; DUMLU, ASIM (My University, 2023)
Taurodontism and root dilaceration are developmental anomalies. Both taurodontism and dilaceration might be related with cleft lip and palate (CLP). This study aimed to investigate the prevalence of taurodontism and root dilaceration, in the children with CLP. Cone beam computed tomography images of 200 children (100 cleft 100 healthy) with CLP were evaluated retrospectively. Taurodontism level was divided into three subtypes as hypertaurodont, mesotaurodont and hypotaurodont. Root dilaceration was recorded if the tooth has completed apexification process. The frequency of taurodontism was found to be 30% in children with CLP and 12% in the control group. The frequency of root dilaceration was found to be 31% in children with CLP and 12% in children without CLP. Incidence of both root dilaceration and taurodontism was found higher in children with CLP (P<0.05). Left maxillary region was found to be the most common localization of both cleft side and root dilaceration (P<0.05). Children with CLP prone to develop dental anomalies such as pulp enlargement and root angulations. Taurodontism and dilaceration are both highly important for preoperative planning. Understanding the causative factors of dental anomalies may increase clinical success.